Mobilizing Science to Break Yield Barriers - Phillips, Ronald L. (Wiley, 2010)
Yield barriers must be broken. The diminished stock of staple foods, higher grain prices, and increases in production failing to keep up with demand, coupled with 80 million people being added to the world population every year, suggests that we are on a collision course with famine unless greater investments are made in research and development, as well as education. Genetic improvement of staples has accounted for more than half of the past increases in yields. Fortunately, a revolution in genetic knowledge is co‐evolving with the increased demand for food, feed, fiber, and fuel. Utilizing genetic diversity has been a mainstay of past production improvements High throughput DNA sequencing, the related bioinformatics, and a cascade of genetic technologies can now be employed to detect previously hidden genetic variability, to understand gene functions, to make greater use of accessions in germplasm banks, and to make breeding schemes more efficacious. The involvement of outstanding scientists who can bring interdisciplinary ideas to the question of how to break yield barriers must be part of the strategy. Educational programs at all levels, even high school, should emphasize the opportunities in international agriculture to build a cadre of dedicated scientists for the future.